Didactic factors of formation of communicative competence of future teachers of economics: theoretical and practical aspect of the problem - Хоцкіна, С. М. (Pedagogy of Higher and Secondary Education, 2012)
Khotskina S. M. Didactic factors of formation of communicative competence of future teachers of economics: theoretical and practical aspect of the problem. In the article the system of concepts in the aspect of the definition of didactic approaches and principles is corrected on the basis of analysis, synthesis, and comparison of scientific information. Specificity of chosen training methods in the process of communicative competence formation of future teachers of economics at pedagogical disciplines studying is grounded.